Femtosecond System with Pulse Pumping of Seed Laser and Amplifier by Using a Single Power Unit - S. A. Tikhomirov (Приборы и методы измерений)
For several decades development of methods for generating ultrashort pulses has been an  independent urgent scientific and technical problem. There is a constant improvement both in the methods of such pulses receiving and in methods of their use. The aim of this work was to investigate the possibility of realizing the coordinated  operation  of  two  fundamentally  different  types  of  pump  lasers for the femtosecond oscillator and amplifier based on one single-lamp laser head and to create on this basis a compact high-power femtosecond system with pulsed pumping and one power unit.The practical implementation of two types of pulsed lasers (nano- and picosecond ones operating, respectively, in Q-switch and modelock regime) on a single laser head with two active elements and one pump lamp is carried out. The required synchronization in time the pump pulse femtosecond amplifier formation and quasi-stationary region of generated pulses in the output radiation of a femtosecond Ti:sapphire is obtained.On this basis a compact, pulse pumped monoblock laser system has been developed that can generate femtosecond pulses with a duration of 50–150 fs with an energy up to 1 mJ and a high enough pulse repetition rate (up to 1 kHz which is determined by the type of laser head and pump unit used). In the developed laser system a compact scheme of a stretcher-compressor with a single common diffraction grating is used.Laser systems of this type characterized by a relatively low cost due to the use of a single power supply unit for simultaneous pumping  of  the  amplifier  and  oscillator,  as  well  as  lower  requirements for the quality of optical elements and usage conditions due to the pulse mode of operation, are quite practical and  can  be  used  both  in  scientific research  in  the  field  of  ultra-high-speed kinetic spectroscopy and nonlinear optics, as well as in numerous technical applications, particular in the precision processing of materials, as optical  simulators  of  the  action  of  heavy  charged  particles  in  testing the radiation resistance of integrated circuits and electronic modules.